2002
DOI: 10.1542/peds.110.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Childhood Asthma: Prevalence, Health Care Utilization, and Mortality

Abstract: Recent data suggest that the burden from childhood asthma may have recently plateaued after several years of increasing, although additional years of data collection are necessary to confirm a change in trend. Racial and ethnic disparities remain large for asthma health care utilization and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
876
1
17

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,052 publications
(937 citation statements)
references
References 31 publications
24
876
1
17
Order By: Relevance
“…This finding is consistent with previous literature: Surveillance programs and epidemiologic studies have consistently shown that Puerto Ricans have higher rates of both wheezing and asthma diagnosis than non-Hispanic White 33 and other US minorities, 34 and this relationship has shown to persist even after controlling for important confounders or socioeconomic measures and housing conditions. 8,10,35 In the current study, lack of health insurance coverage was associated with asthma, even after adjustment for individual, housing, and neighborhood factors. One proposed explanation for this finding is that uninsured children who have temporary and episodic interactions with the healthcare system (e.g., assessments by unfamiliar providers in urgent care settings) may be more likely to be given a diagnosis of asthma for a wheezing episode to ensure treatment.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…This finding is consistent with previous literature: Surveillance programs and epidemiologic studies have consistently shown that Puerto Ricans have higher rates of both wheezing and asthma diagnosis than non-Hispanic White 33 and other US minorities, 34 and this relationship has shown to persist even after controlling for important confounders or socioeconomic measures and housing conditions. 8,10,35 In the current study, lack of health insurance coverage was associated with asthma, even after adjustment for individual, housing, and neighborhood factors. One proposed explanation for this finding is that uninsured children who have temporary and episodic interactions with the healthcare system (e.g., assessments by unfamiliar providers in urgent care settings) may be more likely to be given a diagnosis of asthma for a wheezing episode to ensure treatment.…”
Section: Discussionmentioning
confidence: 43%
“…1 Childhood asthma is a particularly pertinent example of a disease that is "socially patterned" 2,3 : A body of research has shown that asthma is disproportionately shouldered by socially disadvantaged populations, particularly minority children living in low-income urban areas. 2,[4][5][6][7][8] Studies conducted among populations of urban children have explored correlates of childhood asthma in efforts to identify the different levels at which social, psychological, and physical factors in the urban environment increase children's risk for asthma. Parent's race, 9,10 child's gender, 9,10 poverty, insurance status, 11 housing conditions, 10,12,13 and indoor allergen exposures [14][15][16] have all been associated with asthma in children, and some studies have also linked neighborhood level socioeconomic or housing characteristics to asthma.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] African American children with asthma are more likely to report functional disability, 5,6 have two to three times higher outpatient and emergency department (ED) visits, 7 are 93 times as likely to be hospitalized and 94 times as likely to die from asthma compared with white youths 8 and present at the ED with more severe symptoms. 9 Research consistently suggests a complex interplay between individual (e.g., genetic predisposition), family (e.g., parental smoking, socioeconomic status, and maternal stress), and environmental risk factors (e.g., allergen exposure), which undermine asthma management and exacerbate vulnerability to poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common chronic disease in children, the leading noninjury cause of hospitalization for children aged 0-15 years and the most common medical cause of missed school days (Graves and Kozak, 1998;Akinbami and Schoendorf, 2002;Mannino et al, 2002). Asthma prevalence, health service utilization, and mortality have increased among children and young adults in the US since 1980.…”
Section: Introductionmentioning
confidence: 99%
“…From 197575% between to 199375% between -1995, the estimated annual number of pediatric office visits for asthma more than doubled, from 4.6 million to 10.4 million, and the hospitalization rate also increased by 1.4% per year on average. The mortality of childhood asthma increased by 118% between 1978 and 1995 (Gergen, 1992;Mannino et al, 1998;Akinbami and Schoendorf, 2002).…”
Section: Introductionmentioning
confidence: 99%